2022
DOI: 10.1093/ibd/izac253
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vitamin D Supplementation on Disease Course in Inflammatory Bowel Disease Patients: Systematic Review With Meta-Analysis

Abstract: Background The vitamin D role in bone metabolism is well known; however, recent evidence suggests the impact of vitamin D in immune modulation and its implications in immune-mediated diseases, including inflammatory bowel disease (IBD). Method We performed a systematic review with meta-analysis by a specific protocol (PROSPERO: CRD42022311184; March 2022, https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=311184)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…At present, micronutrients for which more clinical trials have been conducted in the IBD population are vitamin D and iron. Vitamin D supplementation in patients with IBD reduces inflammation and the risk of clinical relapse ( 12 , 14 ), improves responsiveness to anti-TNF therapy ( 15 ), prevents upper respiratory tract infections in winter and spring ( 17 ), and may have a positive effect on mental health ( 18 ). However, comparisons between studies are complicated by the wide variation in dose and follow-up of existing clinical trials, and no uniform recommended supplementation dose is currently available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, micronutrients for which more clinical trials have been conducted in the IBD population are vitamin D and iron. Vitamin D supplementation in patients with IBD reduces inflammation and the risk of clinical relapse ( 12 , 14 ), improves responsiveness to anti-TNF therapy ( 15 ), prevents upper respiratory tract infections in winter and spring ( 17 ), and may have a positive effect on mental health ( 18 ). However, comparisons between studies are complicated by the wide variation in dose and follow-up of existing clinical trials, and no uniform recommended supplementation dose is currently available.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose vitamin D supplementation can reduce the expression of proinflammatory cytokines (12), but whether it can alleviate disease activity remains controversial. There is randomized controlled trial (RCT) suggesting that vitamin D supplementation may attenuate disease activity in UC patients (13), but this effect was not observed in the clinical trial conducted by Bendix et al (12) in 40 CD patients. Moreover, a Meta-analysis conducted by Valvano et al ( 14) suggested that vitamin D supplementation can reduce the risk of clinical relapse in IBD patients, especially in CD patients in clinical remission.…”
Section: Vitamins 21 Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In another pooled analysis of 17 trials with 1127 IBD patients, oral vitamin D supplementation effectively increased the concentration of serum 25(OH)D and decreased serum CRP levels, but it did not decrease ESR, disease activity index, and relapse rate [101]. In another recent systematic review with meta-analysis including 12 RCTs, the risk of clinical relapse and disease activity in IBD patients treated with vitamin D supplementation compared with placebo was evaluated [102]. Vitamin D supplementation reduced the overall risk of clinical relapse in IBD patients (ITT: RR, 0.64; CI 0.46-0.89; I 2 = 25% and PP: RR, 0.62; CI 0.41-0.92; I 2 = 18%), especially in CsD patients in clinical remission (RR, 0.47; 95% CI, 0.27 to 0.82; I 2 = 0%).…”
Section: Impact Of Vitamin D Status and Supplementation On Disease Ac...mentioning
confidence: 99%
“…Simply put, patients should be given as much vitamin D as they need to achieve satisfactory levels of circulating 25(OH)D. In a recent meta-analysis, an attempt was made to define a daily vitamin D dosage that is most likely to yield significant results, assuming its effectiveness as adjuvant therapy. Meta-regression suggested that vitamin D dose may indeed influence treatment effectiveness, and it is to be expected to observe this effect with high dose vitamin D regimens [102].…”
Section: Optimal Vitamin D Levels In Ibdsmentioning
confidence: 99%